Trends in hematological cancer in the elderly in Denmark, 1980–2012. (22nd January 2016) - Ocias, Lukas F.; Larsen, Thomas S.; Vestergaard, Hanne; Friis, Lone S.; Abildgaard, Niels; Frederiksen, Henrik
Abstract: Background The number of hematological malignancies is expected to increase as the Danish population ages within the next few decades. Despite this, data on the course of hematological cancers among the oldest patients are sparse with many intervention studies focusing on younger age groups. The aim of this study is to present Danish incidence and mortality rates among older patients with non-Hodgkin lymphomas (NHL), multiple myeloma (MM), chronic lymphocytic leukemia (CLL), and acute myeloid leukemia (AML). Material and methods Nationwide population-based study presenting the incidence, prevalence and mortality rates of NHL, MM, and AML with a focus on the elderly population in Denmark during the last few decades. Data were drawn from the NORDCAN database. Results Incidence rates of NHL, MM, CLL and AML were 10–50 times higher among the population aged 70 years or more than among the younger population. An increasing incidence with stable or decreased mortality rates was seen mainly among elderly patients with NHL during the last few decades, leading to increased survival and a greater prevalence of patients with NHL. Increased relative survival and prevalence could also be seen among elderly patients with MM and CLL, while the trends of the incidence rates were inconclusive for these diseases. Survival among patients with AML improved most notably in those aged below 70 years leading to an increased prevalence of AML patients predominantly in this age group. Conclusion Improvements in diagnostics and treatment have led to increased survival and therefore prevalence of elderly patients with NHL, MM, CLL and AML during the past decades.